2010
DOI: 10.3109/03009734.2010.519446
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of inflammatory markers following cancer-related bowel and liver resection

Abstract: BackgroundMacrophage migration inhibitory factor (MIF) was originally described as a cytokine that inhibits migration of macrophages at the site of inflammation. Subsequently it was also identified as a stress-induced hormone released from the anterior pituitary lobe in response to some pro-inflammatory stimuli like endotoxins and tumour necrosis factor (TNF-α).AimTo compare postoperative changes in serum MIF levels of patients undergoing bowel and liver resections. It has clinical relevance to describe the ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
(21 reference statements)
0
6
0
2
Order By: Relevance
“…Inflammation, malnutrition, and cancer have a close relationship with each other. Malnutrition causes the deterioration of tumor immunity, leading to postoperative complications and cancer progression 3 , 4 . Furthermore, cancer-related systemic inflammation induces catabolism of patients, which causes metastasis 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation, malnutrition, and cancer have a close relationship with each other. Malnutrition causes the deterioration of tumor immunity, leading to postoperative complications and cancer progression 3 , 4 . Furthermore, cancer-related systemic inflammation induces catabolism of patients, which causes metastasis 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Por ello, se puede considerar que en los pacientes incluidos en el estudio la producción de PCR y PCT está directamente relacionada con la intervención quirúrgica, sin la interferencia de las complicaciones posoperatorias. En nuestro estudio se observó que tanto la PCR como la PCT se elevan en todos los pacientes tras la resección hepática, independientemente del tipo de resección realizada, en consonancia con los datos publicados por otros autores [14][15][16][17] . La máxima concentración se alcanza a las 48 h de la cirugía, tanto para la PCR como para la PCT, con una mediana de 13,7 mg/dl y 0,7 ng/ml, respectivamente, y después se produce un progresivo descenso, sin que lleguen a restablecerse los valores preoperatorios durante el periodo de tiempo estudiado.…”
Section: Discussionunclassified
“…Por otra parte, Marton y cols. 16 , encontraron que la PCT alcanzaba su máximo valor a las 24 h de la cirugía, antes que lo observado en nuestro estudio, pero hay que tener en cuenta que los valores correspondientes a las 24 y 48 h fueron muy similares. A la luz de estos resultados, parece que la máxima concentración de PCR y PCT se alcanza entre las 48 y las 72 h de posoperatorio.…”
Section: Discussionunclassified
“…Márton et al. reported elevated serum MIF concentrations in patients after hepatic resection and suggested that the elevation of serum MIF was caused by tissue damage‐related release of MIF from hepatocytes . Pohl et al.…”
Section: Discussionmentioning
confidence: 99%